Lumbung Pangan Sebagai Upaya Ketangguhan Pangan Masa Pandemi Covid-19 Desa Kabuaran Bondowoso - Merissa Pramudita; Devit Dewi Anggraini; Nurul Hidayat; Erisa Yuniardiningsih; Meri Dwi Apriliyanti; Pandan Wangi; Isa Ma’rufi (Multidisciplinary Journal, 2020)
Food becomes the main concern in food reliance effort for the society particularly during the COVID19 Pandemic. To guarantee the food supply, village plays the essential role to ensure the food supply for village, regency, province and the nation. The Act 74 regulation no 6/2014 on village provides an authority for villages to prioritize its budget for development, including primary necessity on food. This research aims at revealing the role of food barn as the attempt to achieve food resilience during the pandemic in Kabuaran Village Grujugan District Bondowoso Regency. The method applied is qualitative with case study. Research area cover Kabuatan Village Grujugan District Bondowoso Regency with the subjects including head village of Kabuaran as the key informant, the village secretary, the treasurers and the head of Covid-19 Task Force as the main informant, Food Barn Cadre as well as those related to food barn management in Kabuaran Village as the supporting informants. Purposive Sampling is used and data were collected primarily by check list and interview dan secondary data includes documents or file from village’s archives. The results shows that the food barn located in Semeru Resilient Village Kabuaran is in good condition as evidenced in the food supply, administration, food supply distribution, recipient line up and well-arranged food distribution and the availability of innovation such as Ginger, lemongrass and sugar. Herbs and traditional medicine plants are well taken care of and used by the villagers. To conclude, the food barn constructs resilient in villagers life particularly during the pandemic covid19. The food barn enables village to be resilient and independent. Keywords: COVID-19, food resilience, food barn